Synthesis, Crystal Structure, HF and DFT Calculations of 1-(2-chlorobenzyl)-N-(1-(2-chlorobenzyl)-4,5-dihydro-1H-imidazol-2-yl)-1H-benzimidazol-2-amine - Yüksektepe, Ç.; Çalışkan, N.; Genç, M.; Servi, S. (Maik Nauka/Interperiodica/Springer, 2010)
The titled compound (1), has been synthesized and characterized by IR and 1H-NMR spectroscopy, and single crystal X-ray diffraction. The compound crystallizes in the triclinic space group P-1. The crystal structure is stabilized by C-H⋯π and aromatic π-π interactions. There are also intramolecular N-H⋯N and C-H⋯N hydrogen bonds in the molecule. The use of quantum chemical calculations to characterise and optimise the choice of material is illustrated by ab initio treatments. Vibrational frequencies and LUMO-HOMO energy difference of 1 have also been investigated by Density functional theory (DFT) and Hartree-Fock (HF) calculations. Calculated frequencies are in good agreement with the corresponding experimental data. © 2010 Pleiades Publishing, Ltd.
Keywords: Benzimidazole; Crystal Structure; DFT and HF Calculations; HOMO and LUMO Energy; IR Spectra